2017
DOI: 10.1159/000485226
|View full text |Cite
|
Sign up to set email alerts
|

Familial Duplication/Deletion of 1q42.13q43 as Meiotic Consequence of an Intrachromosomal Insertion in Chromosome 1

Abstract: Rearrangements of the region 1q42.13q43 are rare, with only 7 cases reported to date. The imbalances described are usually the result of inherited translocations with other chromosomes. Moreover, few cases of both inter- and intrachromosomal deletions/duplications detected cytogenetically have been described. We report the molecular cytogenetic characterization of an inverted insertion involving the region 1q42.13q43 and segregating in 2 generations of a family. The deletion and the duplication of the same seg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…A search of the literature using the PubMed database and the keywords "duplication 4p" OR "trisomy 4p" OR "syndrome 4p" OR "duplication 1q" OR "trisomy 1q" OR "syndrome 1q" OR "complex chromosomal rearrangements", and a search of the Genome Browser database and the DECIPHER platform, found no case with the same set of alterations. However, recombinants with duplications or deletions arising from intra-chromosomal insertions as a result of a crossover in the interstitial or the inserted segment have been well documented for most chromosomes, including chromosome 1 [Madan and Menko, 1992;Jones et al, 2014;Silipgni et al, 2017]. The clinical features are summarized in Table 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A search of the literature using the PubMed database and the keywords "duplication 4p" OR "trisomy 4p" OR "syndrome 4p" OR "duplication 1q" OR "trisomy 1q" OR "syndrome 1q" OR "complex chromosomal rearrangements", and a search of the Genome Browser database and the DECIPHER platform, found no case with the same set of alterations. However, recombinants with duplications or deletions arising from intra-chromosomal insertions as a result of a crossover in the interstitial or the inserted segment have been well documented for most chromosomes, including chromosome 1 [Madan and Menko, 1992;Jones et al, 2014;Silipgni et al, 2017]. The clinical features are summarized in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical phenotype of trisomy 1q (q42qter) in cases involving another chromosome is not properly defined in the literature. Moreover, intrachromosomal insertions are rare phenomena, characterized by the presence of 3 breakpoints and the repositioning of a chromosome segment into another location in the same chromosome [Silipgni et al, 2017], that lead to imbalances, such as deletions or duplications, resulting from recombination within the inserted segment [Nowakowska et al, 2012].…”
Section: Discussionmentioning
confidence: 99%
“…Subjects with duplications suffer from language deficits. Specifically, the child examined by Silipigni et al (2017) showed cognitive and social delay, and said his first words at the age of 2 only. Nonetheless, a detailed characterization of the language problems exhibited by patients with duplications of the distal region of the long arm of chromosome 1 is still pending.…”
Section: Introductionmentioning
confidence: 99%
“…, (Happe, Ronald, & Plomin, 2006), 一些 针对刻板行为和交流障碍的研究已证实了该现象 (Cuccaro et al, 2003;Buxbaum et al, 2001)。所以 Thiel, Driver, & Dolan, 2003;Dani & Bertrand, 2007;Karva & Kimchi, 2014), 胆碱能信号通路异 常与多种精神类疾病的发生有关 (Bowen, Smith, White, & Davison, 1976;Whitehouse et al, 1982; Deng, & Reiner., 2016)。动物模型研究发现胆碱能 Perry et al, 2001;Lee et al, 2002;Martin-Ruiz et al, 2004;Ray et al, 2005;Friedman et al, 2006;Deutsch, Urbano, Neumann, Burket, & Katz, 2010;Petersen et al, 2013) Perrone et al, 2012;Petersen et al, 2013;Soueid et al, 2016)。该基因突变患者会表现出不 同程度的行为异常、认知障碍、言语障碍以及运 动发育迟缓等问题 (Silipigni et al, 2017;Luukkonen et al, 2017) 6(17), 1−8 Bailey, A., Le Couteur, A., Gottesman, I., Bolton, P., Simonoff, E., Yuzda, E., & Rutter, M. (1995). Autism as a strongly genetic disorder: Evidence from a British twin study.…”
mentioning
confidence: 99%